Comparison of Blood and Urinary Cannabis Profiles Between Road Traffic Injury (RTI) and Other Causes of Death in Thai Postmortem Cases - Phuangphung, Peerayuht; Charatprakai, Phasin; Sukata, Siriluck (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aims to compare blood and urinary cannabis profiles between road traffic injury (RTI) and other unnatural causes of death in the Thai population. Methods A cross-sectional study was conducted of Thai postmortem cases where the individual who died was 15 years old or over. Sex, age, cause of death, manner of death, blood alcohol concentration (BAC), and concomitant drugs found were documented for each case. Blood and urinary concentrations of delta9-tetrahydrocannabinol (THC) and its two metabolites, 11-hydroxy-delta9-tetrahydrocannabinol (11-OH-THC) and 11-nor-9-carboxy-delta9-tetrahydrocannabinol (THC-COOH), were analyzed using gas chromatography tandem mass spectrometry (GC-MS/MS). Statistical analysis was performed using the Mann-Whitney U test and Kruskal-Wallis H test. Results A total of 80 subjects were included in this study, comprising 43 RTI and 37 non-RTI subjects. All the RTI cases were motorcycle riders. Blood concentrations of THC, 11-OH-THC, and THC-COOH in the RTI group were significantly higher than those in the non-RTI group (p < 0.01). The number of subjects who had recent cannabis exposure in the RTI group was significantly higher than in the non-RTI group (p< 0.05). Furthermore, the blood concentrations of THC, 11-OH-THC, and THC-COOH in subjects who used cannabis without other drugs of abuse or medications were significantly higher than those in subjects who used cannabis with other drugs of abuse or other medications (p < 0.05). Conclusions Blood THC, 11-OH-THC, and THC-COOH concentrations in RTI cases were significantly higher than in cases with other unnatural causes of death.